Critique of Religious Text Perspective - Luqman Abdul Jabbar; Reviewed by: Syamsul Kurniawan (Al-Albab, 2014)
The phenomenon commonly found in the field of interpretation often portrays the claim of truth. As a result, the truth is hard to define. It is certainly something that is reasonable, given the task instead of a human is not to determine who is right and who is wrong. Only God Almighty who has the right to become the holder of the authority of the truth.